Evaluation of sesame genotypes for field resistance against leaf webber and capsule borer (Antigastra catalaunalis) and gall fly (Asphondylia sesami): SCREENING OF SESAME GENOTYPES TO MAJOR INSECT PESTS - SHALINI PANDEY; MUJAHID KHAN; ANKUR TRIPATHI; NEELAM GEAT; DAN SINGH JAKHAR; RAKESH CHOUDHARY; S R KUMHAR; A K VISHWAKARMA (Journal of Oilseeds Research, 2025)
A study was conducted to evaluate 86 sesame genotypes for resistance under field conditions at Dr BRC Agricultural Research Station, Mandor, Agriculture University, Jodhpur during 2021 and 2022. None of the genotypes was highly resistant to leaf webber and capsule borer (Antigastra catalaunalis). The pooled data on the basis of damage caused to plants, flowers and capsules of sesame genotypes by A. catalaunalis revealed 0.00 to 28.85%, 11.07 to 41.18% and 6.25 to 52.05%, respectively. In both experimental years, 3 genotypes viz., S-0301, NSS and 03-Oct manifested moderate level of resistance to A. catalaunalis at all the three stages of plant growth. These genotypes were also less damaged by A. sesami. However, all the three genotypes were significantly less resistant compare to resistant check (SI-250) against A. catalaunalis. Further, five genotypes viz., NIC-8473, IC-131943, NIC-16248, ES-47, KMR-32-Awere moderately resistant to A. catalaunalis on the basis of flower and capsule damage.